Assessment of Heavy Metal Accumulation and Antibacterial Activity of Some Medicinal Herbs Grown in an Industrial Area of Steel Production, Ahvaz: Assessment of Heavy Metal Accumulation and Antibacterial Activity - Parzhak Zoufan; Roya Jalali; Amer Karimiafshar; Hossein Motamedi (Iranian Journal of Pharmaceutical Sciences, 2017)
Unfavorable conditions can have effect on secondary metabolites production in the plants. The aim of present study was to evaluate the effect of heavy metals accumulation on antibacterial potential of Chenopodium murale L., Senecio glaucus L., Malva parviflora L. and Calendula arvensis L. grown in an industrial area of steel production in Ahvaz, southwest of Iran. The cadmium (Cd), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb) and zinc (Zn) values were analyzed in different parts of these medicinal herbs. The antibacterial activity of methanol and ethanol extracts of the plants was surveyed in standard disc diffusion method against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. In addition, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of these extracts were determined. High concentration of Cd was found in the roots of M. parviflora and S. glaucus. The concentration of other metals in these plants was within the allowed limits. Both of ethanolic and metanolic extracts exhibited the highest antibacterial effect against E. coli and P. aeruginosa. MIC and MBC values of alcoholic extracts were determined against E. coli and P. aeruginosa as the most sensitive bacterial species. It seems that antibacterial activity of studied plants is not essentially correlated with their heavy metal concentration.